Soil and Water Assessment Tool (SWAT) Model: A Systemic Review - Wang, Yinping; Jiang, Rengui; Xie, Jiancang; Zhao, Yong; Yan, Dongfei; Yang, Siyu (Journal of coastal research, 2019)
Wang, Y.; Jiang, R.; Xie, J.; Zhao, Y.; Yan, D., and Yang, S., 2019. Soil and water assessment tool (SWAT) model: A systemic review. In: Guido-Aldana, P.A. and Mulahasan, S. (eds.), Advances in Water Resources and Exploration. Journal of Coastal Research, Special Issue No. 93, pp. 22–30. Coconut Creek (Florida), ISSN 0749-0208. Under the influences of climate change and human activities, the water cycle under changing environment and distributed hydrological model based on physical mechanism have become the focus of hydrology research. Soil & Water Assessment Tool (SWAT) model is one of typical distributed models, and it has been widely used in testing and forecasting the water and sediment circulation and agriculture production with chemicals. The paper used CiteSpace to analyze the research progress based on previous literatures. The results of high frequency keywords and co-word analysis show that the research hotspots of SWAT model include water quality problem, sediment yield, model calibration, uncertainty analysis and sensitivity analysis. The literatures related to SWAT were divided into model application, model accuracy and model coupling. The paper mainly focused on the literature related to model application. The domestic and abroad research processes were reviewed from three hot application fields such as runoff simulation, hydrological impacts under changing environment (HIUCE) and non-point source (NPS) pollution. The results show that: (1) the research content of runoff simulation mainly focused on the adaptability and accuracy of the model; (2) the research content of HIUCE mainly concentrated on analysis of historical changes in hydrological effects and prediction of future changes using the scenario analysis; (3) the research content of NPS pollution mainly focused on the spatial and temporal distribution of nutrients, the influencing factors and degree of nutrients, and the prediction of future to select Best Management Practices (BMPs). The paper pointed out some existing problems, prospected the future research, and proposed research idea of model improvement to adapt to the domestic changing environment. This study should be beneficial to systematically understand the structure, principle, application fields and future development trends of SWAT model, and thus provide references for users of SWAT model in related subjects.